Expedited TR Band Removal for Transradial Approach for Noncoronary Visceral Procedures: Initial Experience. (April 2020) - Shahid, Muhammad; Chandra, Vishnu; Wajswol, Ethan; Contractor, Sohail; Shukla, Pratik; Kumar, Abhishek
Purpose: For transradial interventions, most published studies report an initial Terumo Radial (TR) band placement time of 60 minutes, with gradual deflation over 30 to 90 minutes. We aimed to determine, retrospectively, whether TR band removal time could be expedited to 45 to 60 minutes, without adverse effects via an expedited single-step deflation protocol. Methods: A total of 115 consecutive noncoronary visceral interventions that utilized TR band from September 2017 till February 2019 were retrospectively reviewed. Alternative single-step deflation protocol was utilized where the nursing staff was instructed to deflate the TR band in 1 step between 45 and 60 minutes; 79 patients (43 men, 36 women, mean age of 55.3 ± 13.6 years) underwent 115 transradial interventions. Mean procedure time was 49.8 ± 22.1 minutes, and mean fluoroscopy time was 18.5 ± 10.6 minutes. Data collected included patient demographics, procedure details, and nursing notes on complications including bleeding and reinflation of the TR band. Univariate and Multivariate analyses of independent variables were performed using a binary logistic regression model. All patients were followed up postoperatively before discharge and in clinic upon follow-up. Results: The TR band was deflated at 51.3 ± 14.5 minutes, with successful removal achieved on the first attempt in 103 cases (90.3% primary technical success rate). In 12 cases, bleeding was noted upon initial deflation, secondary technical success was achieved when the band was reinflated for an additional mean time of 37.0 ± 19.1 minutes. There was 1 incidence of radial artery occlusion (0.8%) and 1 incidence of a grade 1 hematoma (0.8%). The only variable predictive of technical outcome upon initial band deflation on univariate binomial logistic regression was initial TR band removal time ( P = .019). Conclusions: A single-step deflation protocol for TR band placement may be safe for nonocclusive patent hemostasis and may translate to even further shorten postprocedural hospital times for patients and cost savings for hospitals.